Aphallia: A case report and literature review - A D Kane; G Ngom; O Ndour; D M Alumeti (Wolters Kluwer Medknow Publications, 2011)
Aphallia is a complex urogenital malformation. It is rarely described in literature. Treatment calls upon feminising genitoplasty in most cases. Authors describe a case in a neonate, insisting on the sociocultural realities which guided their indications.